2018
DOI: 10.1016/j.jacl.2017.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 carboxylic acids in patients with severe hypertriglyceridemia: EVOLVE II, a randomized, placebo-controlled trial

Abstract: An intermediate dose of OM3-CA (2 g daily) significantly lowers TG and non-high-density lipoprotein cholesterol concentrations in patients with SHTG and may benefit individuals at risk of acute pancreatitis and cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 23 publications
1
9
0
4
Order By: Relevance
“…The decrease of VLDL-C concentrations was similar to that of TGs. HDL-C were modestly raised by both treatments, with no extra benefit given by omega-3 [ 106 ].…”
Section: Ppar-α: Fibrates and Omega-3 Fatty Acids In The Metabolicmentioning
confidence: 99%
“…The decrease of VLDL-C concentrations was similar to that of TGs. HDL-C were modestly raised by both treatments, with no extra benefit given by omega-3 [ 106 ].…”
Section: Ppar-α: Fibrates and Omega-3 Fatty Acids In The Metabolicmentioning
confidence: 99%
“…Omega oils are essential fatty acid naturally present in fish, algae, and other seafood; their use as a TG-lowering drug in the management of severe HTG is recommended by both the National Lipid Association [19] and the American Heart Association [20]. The EVOLVE study found a statistically significant reduction in serum TG in patients with severe HTG treated with omega 3 oil 2 g daily in comparison with those treated with olive oil 2 g daily, with a greater treatment effect in patients with very high baseline TG concentrations [21]. The proposed mechanisms to explain these finding include decreased VLDL synthesis by altering transcription factors such as sterol regulatory element-binding proteins involved in triglyceride synthesis and increased triglyceride clearance from the serum by increased lipoprotein lipase activity [22].…”
Section: Discussionmentioning
confidence: 99%
“…Помимо этих ранних работ в научной литературе представлены результаты еще нескольких исследований, в которых применялись ω-3 ПНЖК в различных популяциях пациентов: ALPHA-OMEGA [28], OMEGA [29], SU.FOL.OM3 Study [30], ORIGIN [31], Risk and Prevention Study [32] EVOLVE-I [33], EVOLVE-II [34], ASCEND (A Study of Cardiovascular Events in Diabetes) [35], The Vitamin D and Omega-3 Trial (VITAL) [36], ECLIPSE [37], ESPRIT [38], MARINE [39], ANCHOR [40]. В ряде исследований (EVOLVE-I, II, MARINE, ACNCHOR) изучалось влияние терапии ω-3 ПНЖК на уровень ТГ и безопасность лечения, в ряде крупных рандомизированных исследований (ALPHA-OMEGA, ASCEND,ORIGIN, Risk and Prevention Study, STRENGTH) -влияние на «твердые» конечные точки.…”
Section: основные рандомизированные «исследования-интервенции» с ω-3 пнжкunclassified
“…Новая форма ω-3 ПНЖК (торговое название эпанова) -это смесь ЭПК и карбоновых кислот, зарегистрированная в США в мае 2014 г. У больных с уровнем триглицеридов 2,3-22,5 ммоль / л назначение 4 г эпановы позволяет снизить уровень ТГ на 31 % и уровень ХС-неЛВП на 9,6 % [33,34,37,38]. В исследовании ESPRIT у 627 пациентов с умеренной гипертриглицеридемией (ТГ (2,3-5,6 ммоль / л), получавших базовую терапию статинами, снижение уровня ТГ было более значительным (20,6 %), а уровня ХС-неЛВП -умеренным (6,9 %), без статистически значимых изменений концентрации ХС ЛНП и ХС ЛВП [38].…”
Section: эпанова (эпк + карбоновые кислоты дгк)unclassified